Seasonal and Diurnal Variation of Lightning Over Java Region and Its Relationship with Aerosol - Ahmad Rizqy Shubri; Mutya Vonnisa; Marzuki Marzuki (Postgraduate, University of Mataram, 2023)
This study discusses the influence of aerosols on lightning on Java Island using monthly and diurnal observation data from the Tropical Rainfall Measuring Mission (TRMM) for 16 years (1998 - 2013). Aerosol Optical Depth (AOD) was obtained from The Modern Era Retrospective Analysis for Research and Applications version 2 (MERRA-2). Aerosol and lightning data are grouped into rainy (December-January-February) and dry (June-July-August) seasons and diurnal data grouped per 3 hours. The intensity of lightning strikes in the western part of Java Island, such as Jakarta and Banten, is higher than the eastern region, in accordance with the aerosol distribution pattern. The influence of aerosols and lightning in the rainy and dry seasons is relatively stable. However, influence of aerosols on lightning diurnally changes significantly. The strongest correlation between aerosol and lightning was recorded in the afternoon (r = 0.8) and evening (r = 0.9). Although the influence of aerosols on radiation reaches a saturation point during the day, the movement of land and sea breezes plays a dominant role. At night, the influence of aerosols on surface temperature is weakened due to the absence of solar radiation, so aerosols help the electrification of clouds through the formation of ice crystals.